Failed State. An approach to a “expression” on rise (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The term failed State has become increasingly common language, both politicians and jurists and journalists, since it was coined in 1992. Since then a growing number of states have been classified as failed. The first was Somalia, but others have followed as Afghanistan, Haiti, Iraq and, most recently, Libya or Syria. Given this growing reality aimed to address an approximate expression failed State and the problem involved, forit also analyzed the factors and causes that lead a State to fail in its statehood.
Keywords: State; Failed State; ‘Weberian’ State; Governmental Instability